Got Whey? Sustainability Endpoints for the Dairy Industry through Resource Biorecovery - Giulianetti de Almeida, Maria Paula [UNESP]; Mockaitis, Gustavo [UNESP]; Weissbrodt, David G. (MDPI, 2023)
Whey has applications in food, beverages, personal care products, pharmaceuticals, and the medical sector. However, it remains a massive dairy residue worldwide (160.7 million m3 year−1), with high organic and nutrient loads. About 42% is used for low-value products such as animal feed and fertilizers or is even directly discharged into water streams, leading to ecosystem damage via eutrophication. We reviewed the uses and applications of cheese whey, along with associated environmental impacts and innovative ways to mitigate them using affordable and scalable technologies. Recycling and repurposing whey remain challenges for remote locations and poor communities with limited access to expensive technology. We propose a closed-loop biorefinery strategy to simultaneously mitigate environmental impacts and valorize whey resources. Anaerobic digestion utilizes whey to produce biogas and/or carboxylates. Alternative processes combining anaerobic digestion and low-cost open photobioprocesses can valorize whey and capture organic, nitrogenous, and phosphorous nutrients into microalgal biomass that can be used as food and crop supply or processed into biofuels, pigments, and antioxidants, among other value-added products. The complete valorization of cheese whey also depends on facilitating access to relevant information on whey production, identifying stakeholders, reducing technology gaps among countries, enforcing legislation and compliance, and creating subsidies and fostering partnerships with industries and between countries.
Keywords: anaerobic processes; cheese whey; circular economy; food waste; microalgae